Stock Market Wealth, Private Saving, and the Current Account in the United States: Should We Worry? - Hubert M. Strauß (Kiel Institute of World Economics (IfW), 1999)
The paper investigates by means of cointegration analysis whether the recently observed low levels of private saving and the current account balance in the United States are worrisome in the sense that they cannot be sufficiently explained by determinants which performed well in the past. Stock market wealth of private households is taken into account and turns out to be the main dampening factor of private saving during the nineties. Unlike the current account deficit, which reflects low saving, higher growth with respect to the rest of the world and the high dollar, private saving is much lower than predicted by the model in 1999.
Keywords: F32; H31; E27; E21; 330; Private Saving; Current Account Balance; Stock Market Wealth; Cointegration; Sparen; Leistungsbilanz; Zahlungsbilanzungleichgewicht; Wertpapieranlage; Aktienmarkt; Vermögenseffekt; Aufwertung; Wirtschaftswachstum; Schätzung; Vereinigte Staaten